Multi-Attribute Evaluation and Selection of Broiler House for the Low Prevalence of Footpad Lesion - Garcia,RG (2019)
ABSTRACT Intensive broiler production requires large flock density, which compromises litter quality and increases the prevalence of footpad lesions. The present study aimed at comparing the incidence of footpad dermatitis of broilers reared in two different rearing environments. Data from two broiler houses were recorded during 42 d. Air temperature and relative humidity; litter moisture, pH, and temperature; footpad surface temperature; and the incidence of footpad lesions was investigated. Litter quality was analyzed in a 2 x 4 factorial arrangement, with two house types (dark house or open-sided house) and four rearing phases (21, 28, 35, and 42 d of growth), with four replicates per treatment using 12 replicates. Four replicates were used for analyzing the air environment data. For the footpad lesion identification, a randomly factorial scheme of recording the surface temperature was built (2 x 2) using two houses, and the broiler sex using 15 replicates in the grow-out stages. The measures of association (odds ratio and risk ratio) were calculated. The multi-criteria analysis (Analytic Hierarchy Process - AHP) was applied for estimating the house that provided less prevalence of lesions. The field data did not provide enough evidence for selection of a particular house with less incidence of footpad dermatitis. However, when applying the measures of association data, and corresponding literature data to the AHP, there was an indication that the dark-house provided broiler rearing condition that reduced the incidence of footpad lesions.